동두천시 중앙로 걷고싶은 거리 문화적 활성화 방안 도출을 위한 지역자산 고찰 - 하봉수(Ha Bong Soo), 이승환(Lee Seung Hwan) (한국디자인리서치, 2020)
상업가로의 문화적 활성화를 위해서는 가로를 형성하는 건물과 동식물 그리고 역사나 민속, 가로 형성과정, 사건 등 다양한 소재 및 자원에 대한 탐구가 출발점이 된다. 근본적으로 문화적 거리는 외부공간인 거리에서 일어나는 활동과 그 활동의 장이되는 물리적 시설이라는 두 축이 있을 수 있다. 본고는 동두천시 원도심 일대, 특히 중앙로 가로변을 중심으로 계획하고 있는 물리적 도로개선사업과 병행하여 지역의 차별적 정체성을 창출하기 위한 문화적 활성화 방안도출을 최종목표로 삼고 여기서는 경쟁력 있는 지역자산 도출에 중점을 두었다. 연구는 대상지에 대한 현장조사 및 문화적 도시재생에 대한 이론적 고찰을 토대로 상인대상 설문조사와 시민대상 설문조사를 실시하고, 그 결과를 비교 분석함으로써 지역자산의 도출 및 잠재적 가능성에 대해 고찰하였다. 결과, 도출된 주요 자산은 중앙시장(재래시장)과 전통·향수, 중앙공원 등 휴식·휴게 공간 그리고 구 터미널 등 세 부류로 요약된다. 또한 가로 이미지는 매우 낙후되고 침체된 그리고 특징 없는 거리로 인식하는 경향이 강했고, 시민보다 상인들이 침체 상황을 더욱 심각하게 느끼고 있었다. 특히 젊은 층과 장년층 사이에는 이미지 차이가 확연하고 이를 극복하기 위해서는 청결성, 흥미·재미요소, 세련미 등의 향상 및 개선이 필요할 것이다. 결국, 원도심의 상업가로인 중앙로는 ‘중앙시장’, ‘중앙공원’, ‘구 터미널’ 등 물리적 자산과 비 물리적 자산을 겸비하고 있고, 이러한 자원은 전통과 향수를 간직한 중장년층의 추억을 자극하는 문화 자산임에 틀림없고, 무엇보다 ‘구 터미널’은 물리적 개념을 뛰어넘어 다양한 가능성을 내포한 ‘플랫폼’으로 재해석이 가능하고, 이를 구체화하는 방안이 도출된다면 새롭고 매력적인 젊은 문화를 발산할 수 있는 발전소적 가치를 가지고 있다고 사료된다. For cultural activation of commercial avenue, the starting point should be exploring diverse materials & resources such as history, building, formation process of avenue, shape, case, person, animal & plant, etc borne by the avenue. Basically, cultural street may have 2 axes, namely, activities arising on the street, the external space and physical facilities, the forum of the activities. Taking as the final goal, namely, drawing the method for cultural activation to create region’s discriminatory identity in parallel with physical road improvement project planned mainly around Central avenue, the whole area of original downtown Dongducheon, this paper focuses on drawing competitive regional asset. Based on the local survey of subject area as well as theoretic investigation on the resurrection of cultural city, this study implemented questionnaire to merchants and citizens and investigated drawing regional assets and potential by comparatively analyzing the result. As a result, the mainly drawn assets were summarized into 3 areas, namely, central market (conventional market), tradition & nostalgia, central park, rest place and old terminal, etc. Further, avenue is definitely recognized as quite dilapidated and stagnated and characterless street and its stagnation is recognized more seriously by merchants than citizens. Image difference is quite distinct between youth & middle-aged class. To overcome such difference, it is required to ameliorate & improve cleanness, interesting factors, refinements, etc. After all, it is certain that Central Avenue, the commercial avenue of original downtown keeps physical asset & non-physical assets such as ‘Central market’, ‘Central park’, ‘Old terminal’, etc and such resources are cultural assets which stimulate the reminiscence of middle-aged class who keep tradition and nostalgia. Above all, ‘Old terminal’ can be re-interpreted as platform which includes diverse potentials transcending physical concept. I think that it may have developmental value which can emit new, attractive and young culture if method to concretize such re-interpretation is drawn. KCI Citation Count: 0